SISTEM KEAMANAN BRANKAS BERBASIS ARDUINO UNO - Angga Pratama; Muhammad Fikri; Aan Febriansyah; Irwan Irwan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
At this time the safety system of the safe is the most important thing in our daily lives, both individuals or groups often need protection against security in order to maintain interests in something that is considered important to be guarded. With the passage of time, the development of this technology is getting faster and trying to answer human needs. With today's technology, all human needs are very relative and can be the first layer that protects the contents of the room, that's why a safe must be equipped with security devices that are very easy to use. One example of how to increase a security factor is a safe tool that must utilize Arduino Uno technology as a microcontroller. In this safe security system using a fingerprint sensor and buzzer, this can help users in securing their valuables.